Persepsi Masyarakat Tentang Struktur Makrokosmos dan Simbol Konstruksi Rumah Adat Bugis Berdasarkan Geografi Budaya - Wardiman, Wardiman; Maru, Rosmini; Badwi, Nasiah (LaGeografia, 2020)
This research is included in a qualitative research that aims to determine public perceptions about the structure of macrocosm and symbol of the construction of a Bugis traditional house in Manurungnge village Tanete Riattang sub-district based on cultural geography. Macrocosm is an understanding of Bugis Bone society's trust in the universe that implemented into a form of dwelling. This understanding has been around for decades. After conducting research, it can be concluded that with the times, the understanding of this macrocosm has begun to fade among the people, the structure of the macrocosm is very closely related to the symbol of Bugis traditional house construction, because every time when building a traditional house, the public always includes the symbol of construction on the Bugis traditional house